Aid's impact on democracy - Miguel Ni\~no-Zarazúa; Ana Horigoshi; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper investigates the impact of foreign aid on democratic outcomes using a panel of countries for the period between 1995 and 2018. In so doing, it speaks to a major critique of foreign aid, which is that it negatively impacts democratic governance. The analysis distinguishes between developmental aid and democracy aid, and examines democracy aid to specific sectors, in order to explore variation across different aid types. It draws on the Organisation for Economic Co-operation and Development's (OECD) Creditor Reporting System (CRS) data on foreign aid and indices of democracy from the Varieties of Democracy project, employing a combination of a maximum likelihood estimation and structural equation modelling (ML-SEM) model and fixed effects models. Overall, using a more extensive set of data and methods than previous analyses, we offer comprehensive evidence pointing to aid having a positive if modest impact on democratic outcomes. Our analysis suggests this effect is more significant for democracy aid than developmental aid, but there is no evidence of negative impact for either. These results are robust to multiple specifications.
Keywords: D72; F35; F55; 330; foreign aid; democracy; development